Colheita florestal mecanizada em módulos próprios e terceirizados - Lacerda, Leonardo Cassani (2014)
The objective was to, through this research, conduct a technical analysis of operating machinery used in mechanized harvesting of eucalyptus in four different regions in the states of Espírito Santo and Bahia, with the performance of services by own workforce and outsourced work, as they used similar climate, topography and similar machinery. The machines analyzed were: forest harvester harvester for cutting and the rechargeable skidder forwarder for forwarding. We evaluated the mechanical availability, operational efficiency and degree of machinery use through field collections and database operating efficiency of machines. According to the results, it was observed that in both the own module and in the outsourced, the variables mechanical availability, operational efficiency and degree of use did not differ when analyzed between months, and differentiation occurred between regions. The services performed by own machinery were higher than outsourced, except only the variable mechanical availability for the harvester in regional A and C and the forwarder in the regional A. In the analysis of the total volume produced per year, the total volume in cubic meters (m³), produced by forests cut with own machinery surpassed 1,234,310 m³ in the total volume cut by outsourced machinery in cutting and 1,284,990 m³ the forwarding volume, and such values obtained with the same number of machines (10 harvester's and 4 forwarder´s) per module.